Management centrality in sequential bargaining: Implications for strategic delegation, welfare, and stakeholder conflict - Domenico Buccella; Nicola Meccheri (Global Labor Organization (GLO), 2022)
This paper investigates the issue of strategic delegation by considering the role of management centrality in contracting with different stakeholders. Specifically, a sequential negotiation unionized duopoly model is analysed, in which the management relative bargaining power visà-vis shareholders and vis-à-vis unions can differ. In such a framework, differences in the relative bargaining power among involved stakeholders play a key role in determining the endogenous choice by firms' owners to delegate strategic decisions to the management, or, in other words, the choice of being an entrepreneurial or a managerial firm. Moreover, the distribution of stakeholders' relative bargaining power affects firms' profitability and overall welfare, also leading to novel results with regard to the received literature. In particular, to minimize potential conflict of interests between firms' owners and the overall society, regulation directed to soften the managers' bargaining strength vis-à-vis shareholders must be designed and implemented.
Keywords: D21; L13; L14; 330; management centrality; strategic delegation; unions; bargaining power; social welfare; stakeholder conflict